2000
DOI: 10.1037/0003-066x.55.10.1093
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and culture: Security in the United States and Japan.

Abstract: Attachment theorists maintain that cultural differences are relatively minor, and they focus on universals. Here the authors highlight evidence of cultural variations and note ways in which attachment theory is laden with Western values and meaning. Comparisons of the United States and Japan highlight the cultural relativity of 3 core hypotheses of attachment theory: that caregiver sensitivity leads to secure attachment, that secure attachment leads to later social competence, and that children who are securel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
436
1
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 516 publications
(462 citation statements)
references
References 50 publications
14
436
1
11
Order By: Relevance
“…As noted earlier, culturally-specific principles and expectations for children may both influence and modify children's behavior (Rothbaum et al, 2000). It is unclear the extent to which SBP vary across nations, or across ethnic, racial or cultural groups within nations.…”
Section: Community and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…As noted earlier, culturally-specific principles and expectations for children may both influence and modify children's behavior (Rothbaum et al, 2000). It is unclear the extent to which SBP vary across nations, or across ethnic, racial or cultural groups within nations.…”
Section: Community and Culturementioning
confidence: 99%
“…In addition, contextual factors, such as culture, may also impact the display and reported frequency of sexual behaviors, as culturally-specific values and expectations for children may influence and modify a child's behavior (Rothbaum et al, 2000). The possible role of culture has been examined in three studies, each of which compared rates of reported sexual behavior in European children to American children (Friedrich et al, 2000;Larsson et al, 2000;Schoentjes et al, 1999).…”
Section: Normative Sexual Behaviors In Childhoodmentioning
confidence: 99%
“…For persons with an independent self, attachment security is closely linked with exploration in infancy, and with autonomy later in development (Rothbaum, Weisz, Pott, Miyake, & Morelli, 2000). A defining feature of Western security is trust in new relationships (Rothbaum & Trommsdorff, 2007).…”
Section: Attachment and Emotion Regulationmentioning
confidence: 99%
“…Indeed, in Southern (and South-east) Asia, individuals tend to report higher mean levels of anxious attachment in close relationships compared with Western individuals (Schmitt et al 2004). Furthermore, recent critiques point to the fact that dominant conceptualizations of attachment theory are based on normative, middle-class Western ideals of attachment and 'healthy', or secure, relationships (Rothbaum et al, 2000). However, such an approach ignores the wide variation in relational ideals between cultures (Keller, 2013).…”
Section: Discussionmentioning
confidence: 97%